Management of Decompensated Cirrhosis in the Surgical ICU: an American Association for the Surgery of Trauma Critical Care Committee Clinical Consensus Document. Issue 1 (1st August 2022) - Seshadri, Anupamaa; Appelbaum, Rachel; Carmichael, Samuel P; Cuschieri, Joseph; Hoth, Jason; Kaups, Krista L; Kodadek, Lisa; Kutcher, Matthew E; Pathak, Abhijit; Rappold, Joseph; Rudnick, Sean R; Michetti, Christopher P
Abstract : Management of decompensated cirrhosis (DC) can be challenging for the surgical intensivist. Management of DC is often complicated by ascites, coagulopathy, hepatic encephalopathy, gastrointestinal bleeding, hepatorenal syndrome, and difficulty assessing volume status. This Clinical Consensus Document created by the American Association for the Surgery of Trauma Critical Care Committee reviews practical clinical questions about the critical care management of patients with DC to facilitate best practices by the bedside provider.